Influence of contrast agent dose and image acquisition timing on the quantitative determination of nonviable myocardial tissue using delayed contrast-enhanced magnetic resonance imaging. - Petersen, SE; Mohrs, O; Horstick, G; Oberholzer, K; Abegunewardene, N; Ruetzel, K; Selvanayagam, J; Robson, M; Neubauer, S; Thelen, M; Meyer, J; Kreitner, K (2004)
BACKGROUND: Delayed contrast-enhanced magnetic resonance imaging (ceMRI) has been shown to identify areas of irreversible myocardial injury due to infarction (MI) with high spatial resolution, allowing precise quantification of nonviable (hyperenhanced) myocardium. The aim of our study was to investigate the size of nonviable myocardium quantitatively as a function of time post-contrast when inversion time is held constant in patients post-myocardial infarction using two contrast agent (CA) doses. METHODS: Nine patients with chronic MI underwent two MR scans on a 1.5 Tesla system. Contrast-enhanced MRI data in two short-axis (SA) slices were continuously acquired until 40 minutes after CA injection [gadolinium diethylenetriamine pentaacetic acid (Gd-DTPA), 0.1 mmol/kg body weight = single dose] interrupted only for a complete stack of SA slices encompassing the entire left ventricle (LV) between minutes 20 and 28. Left ventricular mass showing hyperenhancement was determined. The measurement was repeated on the subsequent day with double dose CA (0.2 mmol/kg body weight). Differences of signal intensities for hyperenhanced, nonhyperenhanced myocardium, and LV cavity were calculated. RESULTS: Total mass of hyperenhancement from a complete SA stack acquired between minutes 20 and 28 was lower for single dose CA [9.0% vs. 14.2% for single and double dose, respectively (p = 0.03)]. Ten to 18 minutes after CA injection, there was no significant difference between the two doses and to an internal reference for both single and double dose. For single dose the image contrast between hyperenhancement and LV cavity was superior (minutes 10 to 16, p < 0.05) but inferior between hyperenhanced and nonhyperenhanced myocardium (minutes 6 to 16, p < 0.05). CONCLUSION: Myocardial infarct size measurements are a function of time postcontrast when inversion time is held constant regardless of the contrast agent dose. These data underscore the fact that a standardized imaging protocol that defines how the appropriate inversion time should be selected is needed for comparison of results obtained at various cMR sites.